Предмет: Алгебра, автор: daraaaaaa

пожалуйста помогите!! заранее спасибо ♥️​

Приложения:

Ответы

Автор ответа: solving05
1

Ответ:

Объяснение:

\lim_{x \to \infty} \frac{1}{6x}=0;\\\lim_{x \to \infty} \frac{x+2}{x-1}=\lim_{x \to \infty} \frac{x(1+\frac{2}{x})}{x(1-\frac{1}{x})}=\\=\lim_{x \to \infty} \frac{1+\frac{2}{x}}{1-\frac{1}{x}}=\frac{1}{1}=1;\\\lim_{x \to \infty} \frac{3x^2-2x+5}{2x^2+3x-1}=\lim_{x \to \infty} \frac{x^2(3-2\frac{1}{x}+5\frac{1}{x^2})}{x^2(2+3\frac{1}{x}-1\frac{1}{x^2})}=\\=\lim_{x \to \infty} \frac{3-2\frac{1}{x}+5\frac{1}{x^2}}{2+3\frac{1}{x}-1\frac{1}{x^2}}=\frac{3}{2};

\lim_{x \to \infty} \frac{\sqrt{x^2-2}}{x}=\lim_{x \to \infty} \frac{\sqrt{x^2(1-\frac{2}{x^2})}}{x}=\lim_{x \to \infty} \frac{x\sqrt{1-\frac{2}{x^2}}}{x}=\lim_{x \to \infty} \sqrt{1-\frac{2}{x^2}}=\\=\sqrt{1-0}=1

Похожие вопросы